Direct comparison study between droplet digital PCR and a combination of allele-specific PCR, asymmetric rapid PCR and melting curve analysis for the detection of BRAF V600E mutation in plasma from melanoma patients - Tzanikou, Eleni; Haselmann, Verena; Markou, Athina; Duda, Angelika; Utikal, Jochen; Neumaier, Michael; Lianidou, Evi S. (Clinical chemistry and laboratory medicine, 2020)
Background In metastatic melanoma, 40%-50% of patients harbor a BRAF V600E mutation and are thereby eligible to receive a combined BRAF / MEK inhibitor therapy. Compared to standard-of-care tissue-based genetic testing, analysis of circulating tumor DNA (ctDNA) from blood enables a comprehensive assessment of tumor mutational status in real-time and can be used for monitoring response to therapy. The aim of our study was to directly compare the performance of two highly sensitive methodologies, droplet digital PCR (ddPCR) and a combination of ARMS/asymmetric-rapid PCR/melting curve analysis, for the detection of BRAF V600E in plasma from melanoma patients. Methods Cell-free DNA (cfDNA) was isolated from 120 plasma samples of stage I to IV melanoma patients. Identical plasma-cfDNA samples were subjected to BRAF V600E mutational analysis using in parallel, ddPCR and the combination of ARMS/asymmetric-rapid PCR/melting curve analysis. Results BRAF V600E mutation was detected in 9/117 (7.7%) ctDNA samples by ddPCR and in 22/117 (18.8%) ctDNA samples by the combination of ARMS/asymmetric- rapid PCR/melting curve analysis. The concordance between these two methodologies was 85.5% (100/117). The comparison of plasma-ctDNA analysis using ddPCR and tissue testing revealed an overall agreement of 79.4% (27/34), while the corresponding agreement using the combination of ARMS/asymmetric-rapid PCR/melting curve analysis was 73.5% (25/34). Moreover, comparing the detection of BRAF- mutant ctDNA with the clinics, overall agreement of 87.2% (48/55) for ddPCR and 79.2% (42/53) was demonstrated. Remarkably, the duration of sample storage was negatively correlated with correctness of genotyping results highlighting the importance of pre-analytical factors. Conclusions Our direct comparison study has shown a high level of concordance between ddPCR and the combination of ARMS/asymmetric-rapid PCR/melting curve analysis for the detection of BRAF V600E mutations in plasma.